Producción científica y posicionamiento de universidades según ranking SIR IBER 2013 al 2019, caso latinoamericano (2020)
The SIR IBER Ranking includes the positioning of Latin American universities with at least one publication in the Scopus database for a five-year period. This has served to analyze the scientific activity of regions, countries and universities. This work analyzes the case of Venezuelan universities with respect to their scientific production and positioning according to SIR IBER reports published during the period 2013 to 2019, excluding 2016. Five clusters of universities were designed based on their scientific production. 90% of the country’s scientific publications are concentrated in eight public universities (12%). A decrease of 16% is observed in scientific production and in the positioning of universities, however, scientific leadership stands out in 63%, with an increase of 18% in collaboration with international authors and a production of 47% in access open.